Identification of the Main Aspects of Cooperation Management and the Problems Arising from their Misunderstanding - Josef Vodak; Jakub Soviar; Viliam Lendel (Communications, 2014)
Goal of the article is to identify main aspects of cooperation management, using detailed analysis of available scientific literature together with outcomes of performed empirical research. With the identified main aspects, we were able to identify problematic areas related to the use of cooperation management and to propose a number of recommendations in order to correct these issues. The article thus brings to managers a handy tool in a form of a set of recommendations (instructions) that are meant to support problem-free use of cooperation management within a company.